Sistem Klasifikasi Kualitas Daging Ayam Broiler sebagai Bahan Pembuatan Bakso berdasar Nilai Resistansi dan Kadar Amonia dengan menggunakan Metode Fuzzy - Iqbal Maulana Susanto; Barlian Henryranu Prasetio; Achmad Ridok (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
The availability of chicken meat is inversely proportional to the demand, resulting in meatball producers being unable to choose proper chicken meat. In making meatballs, quality meat is needed that is fresh, firm, and fit for consumption. Then a classification system was created that could detect quality of chicken meat based on the aroma and texture. System input values come from the MQ-135 gas sensor and resistance circuit (voltage divider). Input data is processed using the fuzzy - Mamdani method on Arduino Pro Mini. Processed data is displayed on the Oled ST7789 LCD and the buzzer sound indicator. The system is small in size with a voltage source from the battery, so the classification system is portable. The results of functional testing of the MQ-135 sensor in measuring ammonia gas levels affect the output voltage value by 96.78%. While the voltage range has a measurement of 96.29% with a measurement range of 1K-100KÎ©. Broiler filet breast meat has an average resistance value of 26.32K - 33.92KÎ© and an ammonia content of 5.41 - 7.41 ppm with wet-processed meat, while the average resistance value and ammonia content of dry processed meat is 27.02K - 34.52KÎ© and 5.45 - 7.33 ppm. System accuracy in classifying using the fuzzy - Mamdani method has a proportion of 83.33% in 24 tests.